Standard International Trade Classification—from Spreadsheet to OWL-2 Ontology - Norbert Luttenberger; Jesper Zedlitz (Business & Information Systems Engineering, 2018)
Trade classifications are a necessary prerequisite for the compilation of trade statistics, and they should—beyond that—be regarded as valuable base for the definition of shared controlled vocabularies for linked business data that deal with import, export etc. The Standard International Trade Classification (SITC) provided by the UN Statistics Division is a widely used classification mostly applied for scientific and analytical purposes. SITC—as most other trade classifications—is available today only in text or spreadsheet formats. These formats reveal the inner hierarchical structure of SITC to the human reader, because SITC trade codes are built according to the decimal classification scheme, but unfortunately, SITC's inner structure is opaque to computer applications in text and spreadsheet formats. In this paper, we discuss an approach to set up an OWL-2 ontology for SITC that states subsumption relations between classes of goods. This kind of semantic underpinning of SITC is suited to ease both checking and extending SITC and to derive from it a shared controlled vocabulary for business linked data. We carefully discuss some problems of today's SITC (among them missing inner nodes of the trade code hierarchy), and we motivate several decisions that we took for ontology design. Finally, we introduce the semantic reasoner as a tool for the (at least partial) automatic derivation of structural information for SITC from the trade code building rule. We report on reasoner runtimes observed for different version of the SITC ontology and for different versions of the Pellet reasoner.
Keywords: 330; trade classification; SITC; Web Ontology Language; Reasoning